Pengaruh Model Problem Based Learning Terhadap Penguasaan Konsep IPA dan Keterampilan Berpikir Kritis Siswa Kelas V MI Al-Islam Kota Bengkulu - Herwansyah; Endang Widi Winarni; Agus Susanta (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study aims to determine the influence of the problem-based leraning (PBL) model on mastery of science concepts and critical thinking skills of MI Al-Islam students in Bengkulu City. This research is a quantitative research. The method used is the quasy experiment. The design in this study is The Matching Only Prettest-Posttest Control Group Design. The population in this study was all class V students of MI Al-Islam Bengkulu City. The sample in this study was 27 VB class students as an experimental class and 32 VA class students as a control class. The instrument given in the form of a written test consists of variables mastery of science concepts and critical thinking skills. The results showed that there was a significant influence of the problem-based leraning model on the mastery of science concepts and critical thinking skills of grade V students of MI Al-Islam Bengkulu City.